Identifying sources of per- and polyfluoroalkyl substances (PFAS) in an arid environment with de facto reuse - Steigerwald, Jessica; Trenholm, Rebecca; Quiñones, Oscar; Vanderford, Brett J.; Dickenson, Eric (Frontiers in Environmental Chemistry, 2026)
Lake Mead is the primary drinking water source for the Las Vegas Valley and supplies water to 25 million people in the Lower Colorado River Basin. Historically, Lake Mead per- and polyfluoroalkyl substances (PFAS) concentrations have been low; however, decreasing lake levels from drought may result in increased impact from the Las Vegas Wash (LVW) leading to increased PFAS levels. Thus, there is a need to better map Lake Mead PFAS sources. Herein, samples were collected from (1) Lake Mead, rainwater, and snowmelt; (2) wastewater, groundwater, and stormwater sources to the LVW; and (3) sewershed sampling for two wastewater treatment plants (WWTP) in the Las Vegas Valley. Nineteen PFAS were quantified via liquid chromatography tandem mass spectrometry. Additionally, some samples were either analyzed using non-targeted high resolution mass spectrometry or processed using the total oxidizable precursor (TOP) assay method. Total PFAS in the Boulder Basin area of Lake Mead was 3.84 ng/L and was dominated by short-chain perfluorocarboxylic and perfluorosulfonic acids. The Colorado River was the primary source of PFAS to Lake Mead (65% of total PFAS loading) and the LVW was an important secondary source (27%). Total PFAS in precipitation samples were low (0.329–1.51 ng/L) with rainwater dominated by long-chain perfluoroalkyl acids while only perfluorobutane sulfonic acid (PFBS) was detected in snowmelt. Domestic wastewater was the primary WWTP PFAS source due to high residential and domestic flow contributions (63%–94%) and lack of industry, while laundry and PFAS-containing cosmetics are significant PFAS sources in residential wastewater (i.e., estimated mass flow contributions of 11%, 9.3% and 2.2% for household laundry, shampoo and cosmetic cream, respectively). These results provide a better understanding of the PFAS sources to Lake Mead, and similar systems, and will help inform future efforts to manage PFAS flows to this important drinking water source.